1995
DOI: 10.1126/science.7532321
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Inhibition of HIV-1 Reverse Transcriptase by Nonnucleoside Inhibitors

Abstract: The mechanism of inhibition of HIV-1 reverse transcriptase by three nonnucleoside inhibitors is described. Nevirapine, O-TIBO, and CI-TIBO each bind to a hydrophobic pocket in the enzyme-DNA complex close to the active site catalytic residues. Pre-steady-state kinetic analysis was used to establish the mechanism of inhibition by these noncompetitive inhibitors. Analysis of the pre-steady-state burst of DNA polymerization indicated that inhibitors blocked the chemical reaction, but did not interfere with nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
401
6
5

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 494 publications
(448 citation statements)
references
References 42 publications
36
401
6
5
Order By: Relevance
“…The values of NERT inhibition for virus budded in the presence of EFV were not different before and after the wash procedure, suggesting that this NNRTI remains bound to the RT molecules inside the viral particles. These results agree with reports that named NNRTIs as rapid-equilibrium and tightly binding inhibitors (16,28). NVP is a rapid-equilibrium inhibitor and requires an excess of the drug over the enzyme concentration (27).…”
Section: Discussionsupporting
confidence: 83%
“…The values of NERT inhibition for virus budded in the presence of EFV were not different before and after the wash procedure, suggesting that this NNRTI remains bound to the RT molecules inside the viral particles. These results agree with reports that named NNRTIs as rapid-equilibrium and tightly binding inhibitors (16,28). NVP is a rapid-equilibrium inhibitor and requires an excess of the drug over the enzyme concentration (27).…”
Section: Discussionsupporting
confidence: 83%
“…NNRTIs are clinically approved anti-HIV drugs 36 that bind to a hydrophobic pocket 4 near the polymerase active site of RT to inhibit DNA synthesis allosterically 37 . We examined one such NNRTI, nevirapine, for its effects on the orientational dynamics of RT.…”
Section: Small-molecule Ligands Regulate Rt Binding Orientationmentioning
confidence: 99%
“…Inhibitors of RT fall into two groups: dideoxynucleoside analogues, which (as their metabolically activated triphosphates) cause premature termination of the extending DNA strand, and non-nucleoside inhibitors (NNIs; DeClercq, 1996). Kinetic (Spence et al, 1995) and structural studies have shown that NNIs, which are almost exclusively HIV-1 specific, function by an allosteric mechanism whereby binding of an NNI in an internal pocket of the RT causes distortion of the polymerase active site. The effectiveness of anti-AIDS therapies is compromised by the selection for drugresistant viral populations (Larder & Kemp, 1989;Schinazi et al, 1996).…”
Section: Introductionmentioning
confidence: 99%